2020
DOI: 10.3201/eid2610.202211
|View full text |Cite
|
Sign up to set email alerts
|

Antibody Responses to SARS-CoV-2 at 8 Weeks Postinfection in Asymptomatic Patients

Abstract: RESEARCH LETTERS We compared levels of severe acute respiratory syndrome coronavirus 2 neutralizing antibodies in recovery plasma from 7 completely asymptomatic coronavirus disease patients with those in symptomatic patients in South Korea. We found that serologic diagnostic testing was positive for 71% (5/7) of completely asymptomatic patients, but neutralizing antibody response occurred in all 7 patients. as informing the public about food shortage while reassuring the public that supply will arrive in a few… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
46
2
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 9 publications
2
46
2
3
Order By: Relevance
“…In our cohort, children were more likely to be exposed to SARS-CoV-2 in the home due to fact that their parent(s) worked in healthcare. The findings from this study may therefore provide a greater insight into how younger children react when exposed to SARS- There is evidence from adult serological studies that those with severe illness develop a significantly greater antibody response than those with mild or asymptomatic disease (31)(32)(33).…”
Section: Discussionmentioning
confidence: 88%
“…In our cohort, children were more likely to be exposed to SARS-CoV-2 in the home due to fact that their parent(s) worked in healthcare. The findings from this study may therefore provide a greater insight into how younger children react when exposed to SARS- There is evidence from adult serological studies that those with severe illness develop a significantly greater antibody response than those with mild or asymptomatic disease (31)(32)(33).…”
Section: Discussionmentioning
confidence: 88%
“…There is evidence from adult serological studies that those with severe illness develop a significantly greater antibody response than those with mild or asymptomatic disease. 28–30 This has raised concerns that children, who typically have mild disease, may fail to develop a meaningful antibody response to SARS-CoV-2 infection. More recently, emerging adult data suggest that even asymptomatic adults are capable of mounting a potentially lasting and protective immune response.…”
Section: Discussionmentioning
confidence: 99%
“…Neutralising antibody responses correlated with disease severity in all studies in which this association was tested. 7,43,49,66,76,85,87,[96][97][98] Importantly, the few studies that investigated asymptomatic cases found those individuals were considerably less likely to develop detectable serum neutralising antibody responses than cases with symptoms. With regard to age and sex, evidence was mixed and a limitation across all papers was a lack of statistical adjustment for severity.…”
Section: Correlates Of Neutralising Antibody Productionmentioning
confidence: 99%